How does parental social mobility during childhood affect socioeconomic status over the life course?. (December 2018) - Byrne, Adrian; Chandola, Tarani; Shlomo, Natalie
Highlights: Parental socioeconomic variables have lasting and independent effects on the children's life course occupational earnings. Parental social mobility measures are more powerful predictors of life course occupational earnings than static versions. Father's social class and housing ownership measures have differing relationships with life course occupational earnings. Father's social class mobility reveals greater intergenerational accumulation of social (dis)advantage. Housing ownership mobility increases later life occupational earnings inequalities more so than father's social class. Abstract: The gap in occupational earnings between children from parents of higher versus lower socioeconomic background widens over the life course. This gap can be at least partly explained by family background characteristics in childhood but the extent to which parental social mobility in childhood can provide additional explanatory power is less well researched. This study compares socially mobile and socially stable families in childhood with static measures of parental socioeconomic status with respect to the children's life course occupational earnings using data from the 1958 National Child Development Study. In doing so, this study investigates the extent to which the children's life course occupational earnings are constrained by their parents' (lack of) social mobility during childhood. Furthermore, the strength of intergenerational socioeconomic transmission may depend on specific socioeconomic characteristics of the parents. Therefore, this study explores the influence of changes in childhood socioeconomic characteristics, namely father's social class and housing ownership status, both separately and combined for assessing independent effects, on adult life course occupational earnings whilst also controlling for maternal education, sex and region of residence. Using life course step function multilevel models, the results indicate that parental social mobility predicts life course occupational earnings over and above socioeconomic variables measured when the child was 16. Moreover, the father's social class mobility measure showcases greater intergenerational accumulation of social (dis)advantage. We also demonstrate social mobility during childhood appears to have long lasting and independent effects on life course occupational earnings.